KONSEP VALUE FOR MONEY (VFM) DALAM ARSITEKTUR PENGANGGARAN BERBASIS KINERJA (PBB) DI INDONESIA - Muhammad Unggul Abdul Fattah (LPPM STIE Muhammadiah Bandung, 2025)
This literature review maps the operationalization of Value for Money (VfM) in Performance-Based Budgeting (PBB) in Indonesia during the period 2020–2024. The search was conducted across domestic scholarly databases (SINTA, GARUDA) and official regulatory/policy portals. The study links the 3E dimensions—economy, efficiency, effectiveness—to policy instruments (SBM, SBK, IKPA, SAKIP), data infrastructure (KRISNA–SAKTI), and external oversight (performance audit/VfM audit). The analysis results identify three mutually reinforcing axes of progress. First, the normative-regulatory axis, characterized by harmonization of the PBB and VfM framework through SAKIP evaluation and integration of planning-to-reporting cycles. Second, the process implementation axis, manifested through the reformulation of the Budget Execution Performance Indicator (IKPA) as a proxy for process efficiency. Third, the system connectivity axis, reflected in the integration of the KRISNA–SAKTI platform to clarify the linkage between resource allocation and performance (line-of-sight). The conclusions of this analysis are: (PP1) VfM is operationalized through input cost control (SBM), process efficiency (IKPA) and technical efficiency based on SBK/unit cost, as well as outcomes (SAKIP) supported by key regulatory packages since 2019. (PP2) 3E measurement has been implemented, but systematic triangulation of SBK–IKPA–SAKIP across ministries/agencies/regions remains incomplete. (PP3) Primary drivers include regulatory consolidation, SBM–SBK, KRISNA–SAKTI integration, and performance audits; barriers encompass data interoperability, monitoring-evaluation dualism, non-uniform outcome definitions, limited unit cost data, and analytical capacity constraints. (PP4) Current evidence shows improved process discipline and results orientation, yet causal evidence of PBB's influence on public service quality remains limited due to insufficient micro-data and fragmented process→results analytical pipelines. (PP5) KRISNA–SAKTI strengthens traceability and performance audits provide feedback loops, but full impact requires closed-loop systems linking audit recommendations to IKPA/SAKIP/SBK indicators. The study recommends standardization of sectoral core 3E indicators (SBK–IKPA–SAKIP), institutionalization of evidence-based spending reviews, data interoperability (metadata/API/unique ID), strengthened risk-based auditing, analytical capacity building, and methodological transparency. These recommendations will contribute to accelerating the quality spending agenda (spending better).